Dense and expanding: Urban development and land markets in Chennai, India - David E. Dowall; Paavo Monkkonen (University of California, Institute of Urban and Regional Development (IURD), 2007)
There is growing research literature on urban land and housing markets in India. Over the past five years, detailed studies have been carried out on urban land market dynamics in Mumbai, Bangalore and Delhi. Taken together, these studies provide detailed assessments of urban land development in India, and explore the various effects of urban planning and development control regulation on the spatial development of India's leading urban regions. This paper adds to this discussion by providing an assessment of the land market from data on land values rather than a focus on policy. In addition, it provides four decades of detailed, spatially disaggregated information on land use, population and land values for the metropolitan area. The research presented in this paper uncovers evidence that Chennai exhibits a unique pattern of spatial development for an Indian city of its size; the population in its already dense city center continues to grow, while simultaneously, the metropolitan expands in a low density pattern on the periphery.
Keywords: 330